AGROTECHNOLOGICAL INNOVATION OF THE SALIBU SYSTEM IN LOWLAND RICE CULTIVATION: IMPLICATIONS FOR CROPPING INDEX AND FARMING FEASIBILITY - Kadek Ayu Charisma Julia Dewi; Made Mika Mega Astuthi (International Conference on Multidisciplinary Research Perspective, 2025)
The Salibu rice cultivation system represents an agrotechnological innovation with significant potential to support land intensification by increasing the cropping index (CI) and improving resource-use efficiency. This study aims to analyze the implications of applying the Salibu system on productivity, cropping index, and farm feasibility in lowland rice cultivation. The research employed a descriptive-analytical approach, integrating farm business analysis, revenue–cost ratio (R/C ratio), and direct field observations in farmers’ paddy fields in Tabanan Regency, Bali. The results showed that the Salibu system increased the cropping index from two to three planting cycles per year, with an additional potential yield of 4.92 tons of dry harvested grain (GKP) per hectare annually. Economically, the Salibu system was more efficient, reducing production costs by up to 25.81% compared to conventional transplanting systems, and achieved an R/C ratio of 2.1, indicating farm feasibility. From an agrotechnological perspective, the Salibu system not only delivers economic benefits but also enhances water-use efficiency, reduces dependence on external inputs, and aligns with sustainable agroecological farming practices. These findings highlight that the Salibu cultivation system can serve as a relevant land intensification strategy to address future challenges of food security and climate change.